2015
DOI: 10.1007/s00109-015-1296-9
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development

Abstract: MicroRNAs play a crucial role in the regulation of cell growth and differentiation. Mice with genetic deletion of miR-375 exhibit impaired glycemic control due to decreased β-cell and increased α-cell mass and function. The relative importance of these processes for the overall phenotype of miR-375KO mice is unknown. Here, we show that mice overexpressing miR-375 exhibit normal β-cell mass and function. Selective re-expression of miR-375 in β-cells of miR-375KO mice normalizes both, α- and β-cell phenotypes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 45 publications
2
92
0
Order By: Relevance
“…In the islet transplantation setting in humans where acute β-cell death is observed, Kanak et al [29••] showed that circulating miR-375 levels were elevated immediately post-transplantation and remained elevated up to 7 days later. In the T1D setting, C-peptide-negative individuals exhibited higher circulating miR-375 levels compared to individuals with more substantial β-cell mass, such as non-diabetic controls, individuals with T2D, and individuals with maturity onset diabetes of the young (MODY) [66••]. These findings suggest that steady-state circulating levels of miR-375 are more likely a reflection of dying β-cells rather than prevailing β-cell mass.…”
Section: Non-coding Rnas As Circulating Biomarkers Of β-Cell Stress Imentioning
confidence: 99%
“…In the islet transplantation setting in humans where acute β-cell death is observed, Kanak et al [29••] showed that circulating miR-375 levels were elevated immediately post-transplantation and remained elevated up to 7 days later. In the T1D setting, C-peptide-negative individuals exhibited higher circulating miR-375 levels compared to individuals with more substantial β-cell mass, such as non-diabetic controls, individuals with T2D, and individuals with maturity onset diabetes of the young (MODY) [66••]. These findings suggest that steady-state circulating levels of miR-375 are more likely a reflection of dying β-cells rather than prevailing β-cell mass.…”
Section: Non-coding Rnas As Circulating Biomarkers Of β-Cell Stress Imentioning
confidence: 99%
“…79,[82][83][84] As a result, often PCR cycle numbers (Cq) distributions are skewed relative to actual miRNA copy numbers, even with the latest locked nucleic acid (LNA) technology. [85][86][87][88][89][90][91][92][93] The same multiplex qRT-PCR test can have limits of detection that are different by several orders of magnitude for different virus serotypes. 94,95 The problem of discordant results between different platforms becomes worse in the case of low viral loads.…”
Section: Quantitative Reverse Transcription-pcr (Qrt-pcr)mentioning
confidence: 99%
“…We took advantage of these effects at cones and wedges in the development of AC sprays and nano-aerosolization technologies. [84][85][86][87][88][89] Similarly, these effects may be used for thermal programming in PET conical nanopores. The local Joule heating density increases rapidly towards the tip due to field focusing, rE 2 ¼ rE 2 0 ðR=rÞ 4 , where r is the local conductivity, E 0 is the nominal field proportional to the applied voltage V, and R is the radial position of the base in the spherical coordinate r that traverses the cone axis.…”
Section: -18mentioning
confidence: 99%
“…However, this group also showed that β cell-derived miRNA-375 only contributes to about 1% of the total pool of circulating miRNA-375. Thus, while these authors speculated that increases in miR-375 may provide a reasonable assessment of β cell death, they questioned whether miRNA-375 was capable of providing insight into levels of β cell mass (31). …”
Section: Differentially Expressed Mirnas In Type 1 Diabetesmentioning
confidence: 99%